2004
DOI: 10.1124/jpet.104.068676
|View full text |Cite
|
Sign up to set email alerts
|

Human Urocortin 2, a Corticotropin-Releasing Factor (CRF)2Agonist, and Ovine CRF, a CRF1Agonist, Differentially Alter Feeding and Motor Activity

Abstract: Two corticotropin-releasing factor (CRF) receptor families have been identified (CRF 1 and CRF 2 ). Whereas anxiogenic-like roles for the CRF 1 receptor have been identified, behavioral functions of the CRF 2 receptor remain obscure. Urocortin 2 (Ucn 2), a CRF-related peptide that selectively binds CRF 2 receptors, was recently identified and recognized for its central anorectic properties. The present study tested the hypothesis that the anorexigenic mode of action of Ucn 2 differed from that of ovine CRF (oC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
37
2

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 57 publications
(41 citation statements)
references
References 37 publications
(42 reference statements)
2
37
2
Order By: Relevance
“…This hypothesis is in contradiction to previous conceptualizations of the role of the CRF 2 receptor in ingestive behavior, which have argued that stimulation of this receptor reduces feeding without inducing anxiety-like effects (Zorrilla et al, , 2004, a notion that is based primarily on the finding that intracerebroventricular administration of urocortin2 and urocortin3 can cause delayed reductions in stress-like responses (Spina et al, 1996;Valdez et al, 2002Valdez et al, , 2003Valdez et al, , 2004Venihaki et al, 2004). Yet, multiple studies, in addition to the present findings, indicate that particularly when administered site-specifically into extrahypothalamic regions including the LS, UCN or urocortin2 promotes stress-like behaviors through the activation of CRF 2 receptors (Moreau et al, 1997;Radulovic et al, 1999;Pelleymounter et al, 2000Pelleymounter et al, , 2002Pelleymounter et al, , 2004Spina et al, 2002;Risbrough et al, 2003;Henry et al, 2006).…”
Section: Discussioncontrasting
confidence: 50%
“…This hypothesis is in contradiction to previous conceptualizations of the role of the CRF 2 receptor in ingestive behavior, which have argued that stimulation of this receptor reduces feeding without inducing anxiety-like effects (Zorrilla et al, , 2004, a notion that is based primarily on the finding that intracerebroventricular administration of urocortin2 and urocortin3 can cause delayed reductions in stress-like responses (Spina et al, 1996;Valdez et al, 2002Valdez et al, , 2003Valdez et al, , 2004Venihaki et al, 2004). Yet, multiple studies, in addition to the present findings, indicate that particularly when administered site-specifically into extrahypothalamic regions including the LS, UCN or urocortin2 promotes stress-like behaviors through the activation of CRF 2 receptors (Moreau et al, 1997;Radulovic et al, 1999;Pelleymounter et al, 2000Pelleymounter et al, , 2002Pelleymounter et al, , 2004Spina et al, 2002;Risbrough et al, 2003;Henry et al, 2006).…”
Section: Discussioncontrasting
confidence: 50%
“…The attenuation of all behaviors by blockade of the CRF 1 receptor using antalarmin further supported mediation by the CRF 1 receptor. Moreover, no effect of CRF 2 receptor stimulation with the selective agonist urocortin II was observed on any of the behaviors, with doses that are reported to affect feeding behvior (Zorilla et al, 2004). The role of CRF 1 receptors in grooming is supported by evidence from previous investigations (Bressers et al 1995;de Groote et al 2005;Drago et al 1999;Lumley et al 2001;Ohata and Shibasaki 2004).…”
Section: Characterization Of Crf-evoked Behaviorssupporting
confidence: 59%
“…A caveat to this conclusion is that Ucn 3's anorectic effects are delayed, and the formation of a CTA depends on temporal proximity between the conditioned stimulus and the aversive drug state, so it would be useful to evaluate Ucn 3's actions in a time-insensitive measure of malaise. In this vein, the related CRF 2 agonist Ucn 2 did not increase kaolin clay intake (pica), an unconditioned measure of visceral illness at doses through 10 mg (Zorrilla et al, 2004). Still, it cannot be ruled out that aversive, 'non-visceral' actions of high doses of Ucn 2 (Inoue et al, 2003) that promoted a CTA might be shared by high doses of Ucn 3.…”
Section: Discussionmentioning
confidence: 87%
“…We and others found that i.c.v. Ucn 2 reduced nocturnal food intake (Zorrilla et al, 2004), beginning 3-6 h postinjection in nondeprived rats (Inoue et al, 2003;Ohata and Shibasaki, 2004;de Groote et al, 2005) or mice (Reyes et al, 2001). Ucn 3 (i.c.v.)…”
Section: Introductionmentioning
confidence: 98%